Diversity of Savoryella jones and eaton from north Maharashtra - Patil, S Y; Borse, B D (Journal of Ecobiotechnology, 2012)
The present paper deals with three species of ascomycetous genus Savoryella viz. Savoryella fusiformis Ho, Hyde and Hodgkiss, Savoryella grandispora Hyde and Savoryella limnetica Chang and Hsieh were collected from the submerged wood samples from the various water bodies in North Maharashtra region. All the three species are being recorded for the first time form India. Brief notes and illustration are given for each taxon. Geographical distribution of each species in India is also provided.